The impacts of WTO export subsidy abolition on the agri-food industry in the EU : a preliminary assessment - Kerkelä, Leena; Lehtonen, Heikki; Niemi, Jyrki; Valtion taloudellinen tutkimuskeskus (VATT-keskustelualoitteita, 2005)
Abstract (1 s.).
Keywords: kaupan esteet; avunanto; maatalous; maatalouspolitiikka; EU-maat; bistånd; lantbruk; jordbrukspolitik; EU-länder